A disconnection mechanism of enhanced grain boundary diffusion in Al2O3. (June 2015) - Heuer, A.H.; Zahiri Azar, M.
Abstract : Enhanced diffusion in high angle grain boundaries in Al2 O3 is usually attributed to relatively easy point defect jumping in the plane of the boundary, due to the more open and disordered geometry of random boundaries. However, the pre-exponentials revealed by recent diffusion experiments are incompatible with a point defect mechanism. Instead, such grain boundary diffusion is thought to occur by migration of disconnections, grain boundary ledge defects characterized by a step height h, and a Burgers vector, b .